Do rural incentives payments affect entries and exits of general practitioners?. (October 2018) - Yong, Jongsay; Scott, Anthony; Gravelle, Hugh; Sivey, Peter; McGrail, Matthew
Abstract: Many countries use financial incentive programs to attract physicians to work in rural areas. This paper examines the effectiveness of a policy reform in Australia that made some locations newly eligible for financial incentives and increased incentives for locations already eligible. The analysis uses panel data (2008–2014) on all Australian general practitioners (GPs) aggregated to small areas. We use a difference-in-differences approach to examine if the policy change affected GP entry or exit to the 755 newly eligible locations and the 787 always eligible locations relative to 2249 locations which were never eligible. The policy change increased the entry of newly-qualified GPs to newly eligible locations but had no effect on the entry and exit of other GPs. Our results suggest that location incentives should be targeted at newly qualified GPs. Highlights: Difference-in-differences design is used to study GP rural financial incentives. Overall rural-urban distribution of GPs is unaffected by financial incentives. New GPs are more likely to respond to financial incentives than existing GPs. The findings suggest a targeted approach in incentive design.